Analisis dampak Teknologi AI terhadap Kualitas dan Aksesibilitas Pendidikan di Era Digital - Anton Nurfendi; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
Education in the digital era faces challenges in enhancing the effectiveness and inclusivity of learning. The use of artificial intelligence (AI) technologies, such as generative tools and ChatGPT, offers innovative solutions to these challenges. This research aims to develop an AI education system that supports personalized learning, automated assessment, and cross-disciplinary applications of ChatGPT. The system development method involves needs analysis, AI system design, and technology implementation in the educational context. The research results show that the system can provide relevant learning experiences by tailoring approaches to individual needs. The practical implication is the adoption of the system by educational institutions to improve the quality and accessibility of digital learning.